Microwave Sleep Apnoea Monitoring - Karmakar, Nemai Chandra; Yang, Yang; Rahim, Abdur (Series in BioEngineering, 2018)
This book presents the design, development and field trials of radio frequency based wireless monitoring system for sleep apnoea patients. It contains 4 major areas including general background of wireless monitoring technology and MIMO in wireless body area network (WBAN), microwave hardware designs, virtual MIMO in WBAN and hardware system level implementation and field trials. At components level, this book presents the design theory, process and examples of bandpass filters, lowpass filters, low profile patch antennas, power amplifiers and oscillators which are the key elements in transducer designs in the body area network and cooperative communication wireless sensor network system. At system level, this book features the hardware integration, field trial and network coding techniques. This book also gives a presentation of virtual MIMO applications, e.g. MIMO implementation using FPGA, correlation coefficient measurement and correlation coefficient measurement. The book will create impact in the fields of wireless monitoring technology in biomedical engineering, which have been growing exponentially.